Spotkania . niezależne pismo młodych katolików, no. 33-34, 1987 - Bradel, Zdzisław; Krupski, Janusz; Szaciłowski, Stefan; Ruszar, Józef; Ciszkowski, Józef (s.n.], 1987)
No. 1(1977)-no. 7/8(1979), no. 17(1981)-no. 21/22(1983), no. 27/28(1984) contains contains reprints from: Paris : Editions Spotkania